Morphology and activity relationships of macroporous CuO-ZnO-ZrO2 catalysts for methanol synthesis from CO2 hydrogenation - Wang, Yu-Hao; Gao, Wen-Gui; Wang, Hua; Zheng, Yan-E; Li, Kong-Zhai; Ma, Ru-Gui (Rare metals, 2016)
A series of macroporous CuO-ZnO-ZrO2 （CZZ） catalysts with different Zn/Zr ratios were successfully prepared by template method and characterized by X-ray diffraction （XRD）, N2 adsorption, reactive N2O adsorption, scanning electron microscopy （SEM）, H2 temperature-pro- grammed reduction （H2-TPR）, and transmission electron microscopy （TEM）. The activity of the catalysts was tested for methanol synthesis from CO2 hydrogenation. It is found that the increase in the Zn/Zr ratio could lead to the sintering of the catalysts, destroying the macroporous structure integrity. The macroporous CZZ catalysts own lower Zn/Zr ratio, exhibiting a better morphology and activity. For comparison, the conventional nonporous CZZ catalysts were also investigated. The results show that the CZZ catalysts with macroporous structure own smaller particles, higher CO2 conversion, and CH3OH yield. It reveals that the macroporous structure could inhibit the growth of the par- ticle size, and the special porous structure is favorable for diffusion and penetration of CO2, which could improve the catalytic activities.